LARP4A recognizes polyA RNA via a novel binding mechanism mediated by disordered regions and involving the PAM2w motif, revealing interplay between PABP, LARP4A and mRNA. Issue 8 (1st March 2019) - Cruz-Gallardo, Isabel; Martino, Luigi; Kelly, Geoff; Atkinson, R Andrew; Trotta, Roberta; De Tito, Stefano; Coleman, Pierre; Ahdash, Zainab; Gu, Yifei; Bui, Tam T T; Conte, Maria R
Abstract: LARP4A belongs to the ancient RNA-binding protein superfamily of La-related proteins (LARPs). In humans, it acts mainly by stabilizing mRNAs, enhancing translation and controlling polyA lengths of heterologous mRNAs. These activities are known to implicate its association with mRNA, protein partners and translating ribosomes, albeit molecular details are missing. Here, we characterize the direct interaction between LARP4A, oligoA RNA and the MLLE domain of the PolyA-binding protein (PABP). Our study shows that LARP4A–oligoA association entails novel RNA recognition features involving the N-terminal region of the protein that exists in a semi-disordered state and lacks any recognizable RNA-binding motif. Against expectations, we show that the La module, the conserved RNA-binding unit across LARPs, is not the principal determinant for oligoA interaction, only contributing to binding to a limited degree. Furthermore, the variant PABP-interacting motif 2 (PAM2w) featured in the N-terminal region of LARP4A was found to be important for both RNA and PABP recognition, revealing a new role for this protein–protein binding motif. Our analysis demonstrates the mutual exclusive nature of the PAM2w-mediated interactions, thereby unveiling a tantalizing interplay between LARP4A, polyA and PABP.